Developing Online Materials for Tour Guides - Ratnawati, Sinta Dewi (Journal of ELT Research, 2018)
This English for Specific/Occupational Purpose (ESP/EOP) program was meant to answer the needs of the Indonesian migrant labourers to improve their English for future employment as tour guides. The objectives of this research were to identify the contents that should be in the materials, to investigate the students’ response about the later developed materials, and to study the lacks in the program. The material development process underwent the 7 stages of material development proposed by Nation and Macalister (2010), consisted of analysing the environment and the needs, following principles, setting goals and objectives, choosing contents and sequence, finding the format and presentation, monitoring and assessing, and evaluating the course. However, since it is online learning, the stages had to be combined with the stages specifically for online materials proposed by Hartoyo (2012). Thus, the content and sequence choosing stage consisted of the selection of the types of program, materials, software and tasks. The materials consisted of 2 parts which were the tutorials and the lessons. Using the Task-Based Language Teaching approach (Nunan, 2004), the materials were developed and implemented combined with real time online classes. The students’ responses after the implementation were generally positive, although some improvements were still needed.   Keywords: English for specific purpose (ESP), English for occupational purpose (EOP), material development, online learning, English for tour guides, Task-Based Language Teaching (TBLT)